The Role Of Regulations On Bank Margins In Asean Countries - Taib Khan, Fatin Nur Hidayah (2021)
The objective of this study is to investigate the role of regulations on bank margins in ASEAN countries during the period from 2009 to 2017. This study also compares the effect of regulation variables and capital regulations bank margins for both conventional and Islamic banks. Lastly, this study examines the effect of Islamic regulations on Islamic banks' margins. This study utilizes the Generalised Method of Moments and Fixed effects. Firstly, the results show that the regulation variables (activity restrictions, supervisory power, and private monitoring) significantly impact bank margins in ASEAN countries.